Trajetórias de mulheres agricultoras que se tornaram lideranças políticas: resistências e conquistas - Santos, Aline Maiara Demétrio (2019)
In this dissertation we analyze the trajectories of two women farmers, Luciana Guzella Rafagnin and Zelide Cattelan Possamai, who were constituted as political leaders in the Southwest region of Paraná in the period between 1980 and 1990. In this sense, we try to understand what practices have permeated in their trajectories when political leaders, including gender issues, family agriculture, and the history of peasant struggles in the region that gave meaning to their experiences. The methodological course was based on qualitative research, in which the oral narratives were used through individual interviews, as well as the documentary analysis of public archives of the Association of Studies, Guidance and Rural Assistance (ASSESOAR) and participant observation in activities and events in 2017 and 2018, in which the women surveyed were present. From this, the analysis was based on the problematization of gender relations and the meaning of the work in relation to the rural women, observing which mechanisms made our interlocutors of the research constituted themselves as political leaders. We start from the discussion about productive and reproductive work in rural areas and then understand the meaning of leadership and political representation, permeated by the notion of identity, making us understand the intersectional relations from their plural identities. Another point of analysis runs through the networks and resistance strategies of Luciana and Zelide, in which we can perceive the trajectories that intersect with collective history at national and regional level in the period of redemocratization of the country after 1988, since they narrate , in its trajectories, the struggles and achievements made in the period. From this, the analysis of trajectories allowed us to recognize their processes of subjectivation before their constitutions as leadership, allowing us to understand issues that made them R-exist. In this sense, Luciana and Zelide formed as leaderships from the Catholic Church, the Rural Workers' Unions and ASSESOAR by Francisco Beltrão and a network of family support and friendships. As a theoretical perspective, we use the Decolonial Studies, which support us from concepts such as coloniality of knowledge / being / power, active subjectivity, colonial wound, territoriality among others, that strain us to reflect on the relations between colonized peoples, as in Latin America. From this perspective we observe the effects of modernity on women farmers and which mechanisms of resistance are built by subjects marked between what escapes and what approaches the logic of modernity, as well as the trajectories of Luciana, Zelide and so many other women farmers who held positions of political leadership.